Pre-applied mechanical bonded waterproofing membranes: Macroscopic nonwoven behavior during the concreting process. (January 2022) - Heinlein, Ulli; Freimann, Thomas
Abstract: Pre-applied bonded waterproofing membranes are used as positive-side waterproofing membranes on concrete basements. They are installed prior to concrete works and form a bond with the fresh concrete, inter alia, by the use of nonwovens. However, it is not yet known how the nonwovens behave during the concreting process, which is preventing any optimization. This is why this article aims to understand the macroscopic changes of nonwovens during concreting and identifies beneficial nonwoven properties for a waterproof bond. Seven nonwoven bonded pre-applied membranes are installed using fresh concrete and varying installation parameters and are afterward investigated using microsections, hydrostatic tests and micro-CT scans. During the installation process, the nonwovens are first compressed due to the fresh concrete load and behave like exposed to a mechanical load. Then, as vibration compaction begins, cement paste separates from the fresh concrete in a filtration process and fills the nonwoven. The fresh concrete pressure is then transferred via the cement paste so that the nonwovens can decompress due to the residual stress of the fibers. The final nonwoven thickness depends on compaction equipment, compaction time, and orientation of the nonwoven in the concrete. With the onset of compaction, the porosity within the nonwoven decreases fast so that acceptable lateral water migrations are present after 2–3 s using strong compaction equipment. The void volume of the nonwoven is decisive for the compaction time needed, so new nonwovens should be designed with low void volumes concerning a waterproof bond. Highlights: The behavior of nonwovens of pre-applied membranes during concreting was investigated. Seven membranes were examined using microsections, hydrostatic tests, and micro-CT scans. Nonwovens are first compressed and then decompressed during cement paste filling. Optimal macroscopic nonwoven properties for the waterproof bond were identified. Nonwovens with low void volume achieve a waterproof bond more quickly.